Deep Galaxy Stellar Mass Functions As a Function of Star Formation Rate in the Virgo Cluster Environment - Cameron R. Morgan; Elizaveta Sazonova; Ian D. Roberts; Michael L. Balogh; Joel Roediger; Laura Ferrarese; Patrick Côté; Alessandro Boselli; Matteo Fossati; Jean-Charles Cuillandre; Stephen Gwyn (The Astrophysical Journal)
We analyze deep ( M _* ≳ 10 ^7 M _⊙ ) galaxy stellar mass functions (SMFs) of the Virgo cluster using stellar masses derived as part of the Next Generation Virgo Survey. The total SMF has a slope of $α =-1.3{5}_{-0.02}^{+0.02}$ , which is similar to or steeper than typical field values. Using deep H α data from the Virgo Environmental Survey Tracing Ionised Gas Emission we separate out star-forming galaxies, quiescent galaxies with no ongoing star formation, and low star formation rate (SFR) galaxies that are intermediate between these two populations. For each of these populations, the shape of the SMF is found to be universal throughout the cluster, from the core to the outskirts. The star-forming and quiescent SMFs show stark differences with values seen in field galaxies. The relative fraction of quiescent galaxies is highest in the core of the cluster, with low-SFR and star-forming galaxies more significant in the outer regions of the cluster. At low stellar masses ( M _* ≲ 10 ^9 M _⊙ ), the quiescent fraction in the main cluster is significantly higher than that of the field and even satellites of massive groups. At high stellar masses, the quiescent fraction is similar to other studies of cluster galaxies. We model the quiescent population in the infall region of the cluster as a combination of backsplash and field quiescent galaxies, and find that the backsplash fractions needed to explain the observed population are unrealistically high. This suggests the existence of a third population of low-mass galaxies that are preprocessed outside the virial radius of the cluster, possibly in groups prior to infall.